Does persistent anti-HBc positivity influence the prognosis of HBsAg-negative hepatocellular carcinoma? comparative outcomes of anti-Hbc positive versus anti-Hbc negative non-B non-C HCC. Issue 2 (February 2019) - Law, Jia Hao; Tan, Jarrod Kah Hwee; Wong, Kien Yee Michael; Ng, Wan Qi; Tan, Poh Seng; Bonney, Glenn Kunnath; Iyer, Shridhar Ganpathi; Krishnakumar, Madhavan; Kow, Wei Chieh Alfred
Abstract: Background: To compare the presentations and outcomes of anti-HBc seropositive Hepatocellular Carcinoma (HBc-HCC) with anti-HBc seronegative (NHBc-HCC) patients in HBsAg negative Non-HBV Non-HCV (NBNC-HCC) HCC population. Methods: 515 newly diagnosed HCC patients from January 2011 to September 2016 were retrospectively reviewed. 145 (66.5%) NHBc-HCC and 73 (33.5%) HBc-HCC patients were identified. Patient demographics, disease characteristics, details of treatments, recurrence and survival outcomes were analysed. Results: A significantly lower proportion of HBc-HCC patients were diagnosed through surveillence (6.8% vs 26.2%, p = 0.001). HBc-HCC patients were less likely cirrhotic ( p < 0.001), portal hypertensive ( p < 0.001), ascitic ( p = 0.008) and thrombocytopenic ( p = 0.003). A higher proportion of HBc-HCC patients had treatment with curative intent (46.6% vs 30.3%, p = 0.018) and surgery (39.7% vs 16.6%, p < 0.001). Although HBc-HCC patients had larger median tumor size (74.0 mm vs 55.0 mm, p = 0.016) with a greater proportion of patients having tumors ≥5 cm, there was no difference in the overall median survival (19.0 months vs 22.0 months, p = 0.919) and recurrence rates (38.2% vs 40.9%). Conclusion: Isolated anti-HBc seropositivity in HbsAg negative patients tend to present incidentally with delayed diagnoses resulting in larger tumors, but their long-term survival remain comparable.